Enhanching Students’ Reading Comprehension of Scientific Text by Using KWL Charts for Senior High School - Muhammad Satria; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2019)
This paper deals with the use of KWL charts as Know, Want, and Learned (what is known, what is known, and what has been learned) in enhancing students’ comprehension of reading scientific texts in Senior High School students. KWL charts can be used by teachers to make learning English more enjoyable. The use of this KWL chart is used as a solution for teachers to solve students' problems in reading texts, especially scientific forsenior high school students.KWL charts helps the teachers in teaching reading scientific text more interesting, so that it will motivate students to comprehend the text.Giving a table consisting of 3 columns, K, W, and L, which column K is for background knowledge, column W for something unknown or form of a question for the child, and column L for conclusion about what the student has learned or questioned earlier in column W of the scientific text given. These methods or KWL charts are suitable for application in high school to all classes.